SOSIALISASI DIGITALISASI MARKETING DAN INOVASI KEMASAN BAGI UMKM BERKEMBANG DAN NAIK KELAS (DIGEMAS) DI DESA BRUNOSARI (SOCIALIZATION OF DIGITAL MARKETING AND PACKAGING INNOVATION FOR MSMES TO GROW AND UPGRADE (DIGEMAS) IN BRUNOSARI VILLAGE) - Indah Rahayu, Trajuingtyas Adhi Noer Wulandari; Anita Rinawati; Isnaeani Mardiyanti; Iska Ikhtifa Dzaty; Ummu Hannik; Zulfan Hanif (Jurnal Berdaya Mandiri, 2025)
Kalicurug Hamlet, Brunosari Village, is a remote area in Purworejo with lucrative business potential, but still lacks knowledge in marketing and product packaging. The community and MSMEs are largely unaware of digital marketing and packaging innovation. The DIGEMAS Socialization activity aims to improve the understanding and skills of MSMEs in utilizing digital marketing and developing product packaging innovations to compete in the market. This socialization explained digital marketing through e-commerce platforms (Shopee & TikTok Shop) and the importance of product packaging innovation. This socialization demonstrated a significant increase in understanding among participants and MSMEs regarding digital marketing, packaging innovation, and product labeling. The results of the activity demonstrated increased insight and motivation among MSMEs to implement digital technology and improve their product packaging as a step towards further development and advancement. Keywords: MSMEs, Digitalization, Innovation, E-Commerce